2010
DOI: 10.1073/pnas.0911700107
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone decreases trust in socially naïve humans

Abstract: Trust plays an important role in the formation and maintenance of human social relationships. But trusting others is associated with a cost, given the prevalence of cheaters and deceivers in human society. Recent research has shown that the peptide hormone oxytocin increases trust in humans. However, oxytocin also makes individuals susceptible to betrayal, because under influence of oxytocin, subjects perseverate in giving trust to others they know are untrustworthy. Testosterone, a steroid hormone associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
132
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(138 citation statements)
references
References 52 publications
(72 reference statements)
6
132
0
Order By: Relevance
“…Indeed, we tested our BLA-damaged and matched control subjects with an adapted and validated version of the Adolphs et al (33) facial trustworthiness task (36) and found no group differences (Mann-Whitney test, P = 0.47, n = 15, twotailed). Furthermore, in agreement with the above findings of low expectations of monetary return in the trust game, the ratings of trustworthiness of BLA-damaged and control subjects were very low compared with other studies using this task (36,37).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we tested our BLA-damaged and matched control subjects with an adapted and validated version of the Adolphs et al (33) facial trustworthiness task (36) and found no group differences (Mann-Whitney test, P = 0.47, n = 15, twotailed). Furthermore, in agreement with the above findings of low expectations of monetary return in the trust game, the ratings of trustworthiness of BLA-damaged and control subjects were very low compared with other studies using this task (36,37).…”
Section: Resultsmentioning
confidence: 99%
“…Other recent research suggests that the administration of T can induce reductions in trustworthiness evaluations from unfamiliar faces (Bos et al, 2010), and this reduction in perceived trustworthiness appears to be mediated by an increased activation in the amygdala, as well as a reduction in functional connectivity between the amygdala and the orbitofrontal cortex . Taken together, these findings suggest that T, at both circulating levels and following administration exogenously, can influence activation in various brain structures implicated in emotional reasoning and decisionmaking, which may be particularly relevant in studying the link between T and men's context-dependent preferences for opposite sex partners that vary on dimensions of facial sexual dimorphism.…”
Section: Testosteronementioning
confidence: 95%
“…There are very few studies investigating the effects of exogenous manipulations of T on economic behavior, and most have focused on female, rather than male behavior M A N U S C R I P T ACCEPTED MANUSCRIPT 4 (Zethraeus et al, 2009;Bos et al, 2010;Eisenegger et al, 2010;van Honk et al, 2012;Boksem et al, 2013). Some exceptions of recent work involving T administration in healthy men include Zak et al (2009), who report suggestive evidence that it decreased generosity, 1 Wibral et al (2012) who found that it reduced lying, Carré et al (2015) who showed that it impaired socio-cognitive ability only in subjects with low 2D4D or low psychopathic traits, Cueva et al (2015) who found that it increased risk-taking in an investment task, and Carré et al (2016) who found that it led to greater aggression only in subjects scoring high in trait dominance or low in trait self-control.…”
Section: Introductionmentioning
confidence: 99%